2000
DOI: 10.1302/0301-620x.82b8.9864
|View full text |Cite
|
Sign up to set email alerts
|

The skeletal response to matt and polished cemented femoral stems

Abstract: We studied the effect of the surface finish of the stem on the transfer of load in the proximal femur in a sheep model of cemented hip arthroplasty. Strain-gauge analysis and corresponding finite-element (FE) analysis were performed to assess the effect of friction and creep at the cement-stem interface. No difference was seen between the matt and polished stems. FE analysis showed that the effects of cement creep and friction at the stem-cement interface on femoral strain were small compared with the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The implant stem and bone/cement meshes were congruent at their interface, which was modeled with a contact pair containing 1512 quadratic contact and target elements. This interface was bonded in the intact case and modeled with Coulomb friction in the implanted case, using a static coefficient of friction of 0.2 [28].…”
Section: Finite Elementmentioning
confidence: 99%
“…The implant stem and bone/cement meshes were congruent at their interface, which was modeled with a contact pair containing 1512 quadratic contact and target elements. This interface was bonded in the intact case and modeled with Coulomb friction in the implanted case, using a static coefficient of friction of 0.2 [28].…”
Section: Finite Elementmentioning
confidence: 99%
“…Both models are considered to be suitable for studies of this type. Other authors have confirmed sheep to be an appropriate model for hip arthroplasty (Phillips et al 1987, Brumby et al 1998, Barker et al 2000). The bony acetabulum of the sheep is made up of the 3 bones of the pelvis, as it is in man.…”
Section: Introductionmentioning
confidence: 86%
“…Clinical studies have shown that creep deformation is essential for the optimum performance of cemented hip prostheses that achieve stable fixation through taper-locking of the femoral stem within the cement mantle [10][11][12][13][14][15][16]. A number of studies have used finite element analysis (FEA) to investigate the effects of cement creep on the distribution of stresses within the cement, as well as on the magnitude of the micromotion of the stem in the cement mantle [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These difficulties might be one of the reasons that none of the published FEA models of cemented hip prostheses have attempted to calculate the creep component of the deformation of the cement mantle using step-wise integration over a typical hip loading profile. Rather, previous investigators have used simplified load profiles [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%